IMPLEMENTASI PENGELOLAAN KUALITAS PELAYANAN JAMAAH HAJI DAN UMRAH TERHADAP MINAT CALON JAMAAH DAKAM PERSPEKTIF EKONOMI ISLAM - Bahrum Mutakin; Hasan Basri; Ismi Dara Oktavianda (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
This research is motivated by the fact that there are many similar products selling Umrah packages, the development of which is very fast compared to others, where the quality of the product and service for the interest of prospective pilgrims can be an advantage of the product that will be offered as well as the interest of prospective pilgrims to buy it. The purpose of this research is to find out how to manage product quality and the services provided by looking at the number of similar products sold by competitors, because the same competitors are selling these products closely. Here, the researcher wants to know what factors make this Umrah package continue to be superior in terms of quality. product quality and service. The method used in this research uses a descriptive qualitative approach and case study, by describing and illustrating existing phenomena. Data collection techniques in 3 ways, namely: Observation, interviews and documentation. The results of this research show that: 1) Product quality management in this Umrah package has advantages in the product quality of the Umrah package, both in terms of consistent service and providing comfort, the use of attractive Umrah packages and love for the environment, namely using paper materials and the best possible design. by providing pictures on the Umrah package as well as correct information about the product, as well as very cheap prices with very good products. 2) Service to the interests of prospective pilgrims at Tasikmalaya Umrah Travel regarding the services provided by customers/prospective pilgrims is quite satisfactory, where Tasikmalaya Umrah Travel really prioritizes service so that its Umrah packages continue to develop even though there are many competitors. 3) Management of product and service quality towards the interests of prospective pilgrims from an Islamic economic perspective at Tasikmalaya Umrah Travel, where the product owner has provided good and fair product quality to prospective pilgrims. The quality products they provide so far do not have low quality or defects that are not in accordance with Islamic teachings, because if this happens it could be detrimental to prospective pilgrims. Where Tasikmalaya Umrah Travel also has a Halal certificate regarding the products sold so that prospective pilgrims feel they have gained trust, especially prospective pilgrims who are Muslim.